Assessing biodiversity and regulatory ecosystem services in urban water bodies which serve as aqua-Nature-based Solutions - Martín Muñoz, Silvia; Schoelynck, Jonas; Tetzlaff, Doerthe; Debbaut, Robrecht; Warter, Maria; Staes, Jan (Frontiers in Environmental Science, 2024)
In sight of a growing urban population and intensified extreme weather events, cities must integrate in their urban planning elements to both reduce their impact (i.e., air and water pollution, degradation of habitats, loss of biodiversity) and increase their resilience to climate change. In contrast to engineering solutions, which normally not only fail to adequately address these issues but often also exacerbate them, Nature-based Solutions (NBS) are an efficient strategy which can help cities become more sustainable. Aqua-Nature-based Solutions (aNBS) tackle water-related hazards by enhancing water regulation and mitigating flood and drought impacts. However, under a warming climate, aNBS are expected to often dry-out, changing the biodiversity and the ecosystem services they support. The aim of this study is to compare the biodiversity of temporarily and permanently wet urban waterbodies which function as aNBS. We selected two pond complexes with different hydroperiods (therefore, different duration, amplitude and frequency of inundation) and studied the riparian vegetation and aquatic macroinvertebrate biodiversity. The Multimetric Macroinvertebrate Index of Flanders was used to determine the macroinvertebrate biodiversity and to assess water quality of the ponds. Using water stable isotopes and piezometers, the hydrological dynamics were also studied in order to identify the water regulating ecosystem services these ponds deliver. The results showed that the selected pond complexes have a high plant biodiversity, particularly in temporary ponds. Water quality ranged from moderate to poor and macroinvertebrate biodiversity tended to be greater in permanent ponds. Plant and macroinvertebrate alien species were also found in the aNBS. Regarding water regulating ecosystem services, the pond complexes enhanced infiltration and groundwater recharge, providing resilience to both flooding and drought. Our findings corroborate previous studies on the need of diversifying urban ponds' hydroperiods to support biodiversity. Thus, integrating well-designed aNBS into urban planning might be a way to make cities more resilient to water climate-related hazards while enhancing biodiversity.